2020
DOI: 10.1101/2020.01.09.900027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical investigation of microbial quorum sensing under various flow conditions

Abstract: 10Microorganisms efficiently coordinate phenotype expressions through a decision-making 11 process known as quorum sensing (QS). We investigated QS amongst heterogeneously 12 distributed microbial aggregates under various flow conditions using a process-driven numerical 13 model. Model simulations assess the conditions suitable for QS induction and quantify the 14 importance of advective transport of signaling molecules. In addition, advection dilutes signaling 15 molecules so that faster flow conditions requi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Pore scale reactive transport analysis revealed that the macroscopic rate estimates are largely determined by flow conditions and reaction kinetics, and to a lesser extent by the distribution of microbial aggregates. We further evaluated physicochemical conditions effectively coordinating microbial phenotype expression mediated by signaling molecules [2]. Modeling results show that advection dilutes signaling molecules so that faster flow conditions require higher microbial densities, faster signal production rates, or higher sensitivities for effective communication through signaling molecules.…”
mentioning
confidence: 99%
“…Pore scale reactive transport analysis revealed that the macroscopic rate estimates are largely determined by flow conditions and reaction kinetics, and to a lesser extent by the distribution of microbial aggregates. We further evaluated physicochemical conditions effectively coordinating microbial phenotype expression mediated by signaling molecules [2]. Modeling results show that advection dilutes signaling molecules so that faster flow conditions require higher microbial densities, faster signal production rates, or higher sensitivities for effective communication through signaling molecules.…”
mentioning
confidence: 99%